ANALYSIS OF STUDENTS’ ERRORS IN SOLVING CURVED FACE THREE-DIMENSIONAL PROBLEMS BASED ON KASTOLAN’S STAGE REVIEWED FROM FIELD DEPENDENT AND FIELD INDEPENDENT COGNITIVE STYLES: ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL BANGUN RUANG SISI LENGKUNG BERDASARKAN TAHAPAN KASTOLAN DITINJAU DARI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Yudianto, Erfan; Dinia, Liski Roswita; Sugiarti, Titik; Kurniati, Dian; Lestari, Nurcholif Diah Sri (MaPan : Jurnal Matematika dan Pembelajaran, 2022)
This study aims to analyze the types of errors made by students in solving curved face three-dimensional problems based on Kastolan’s stages reviewed from field-dependent and field-independent cognitive styles. This study uses descriptive research with a qualitative approach. The subjects in this study were 4 students of class IX A SMP Muhammadiyah 1 Jember who had completed the cognitive style test and soblukan ethno mathematical story questions, then continued with interviews to obtain more in-depth information. The subject was chosen based on the work of students who made the most mistakes according to the Kastolan error stage indicator. The results obtained in this study are field-dependent students mostly make conceptual, procedural, and technical errors. The form of conceptual error experienced was that students misinterpreted the problem in the form of pictures, students did not conceptualize the height of the cone, and students misinterpreted the shape of the cylinder. The form of procedural error experienced was wrong in determining the formula and students were wrong in determining the surface area of ​​the soblukan’s lid. The form of technical error experienced, students were wrong in doing calculations. The field-independent students made more technical errors. The form of technical error is that students are wrong in doing calculations. Through this research, it is expected that teachers can design learning to minimize student errors in solving problems by looking at the types of errors that have the most.